Ultrasound waves for assessing the technological properties of Pinus caribaea var hondurensis and Eucalyptus grandis wood - Gomes Ribeiro, Patricia; Carlos Gonçalez, Joaquim; Gonçalves, Raquel; Faustino Teles, Ricardo; de Souza, Frederico (Maderas. Ciencia y Tecnología, 2025)
The forest sector plays an important role in the economy and, in these times of sustainability, industries need to save natural resources and leverage them as best as possible in order to achieve excellence in product quality and win the consumer market. The use of advanced technologies and improvement in pre-existing techniques is the most efficient way to understand the raw material, and improve the quality of products manufactured and their rational use. The use of nondestructive technologies has proven effective in characterizing and assessing wood quality. This work aims to predict certain physical and mechanical properties of Pinus caribaea and Eucalyptus grandis, using ultrasound. The research was conducted at the University of Brasilia (UNB), in conjunction with the Forest Products Laboratory (LPF/SFB) and the State University of Campinas (UNICAMP/SP). The results permit us to state that certain physical-mechanical properties of these species can be predicted with ultrasound. The property best estimated is density, followed by modulus of elasticity and modulus of rupture.